Congenital cystic adenomatoid malformations of the lung: a retrospective study of diagnosis, treatment strategy and postoperative morbidity in surgically treated patients. (20th September 2022) - Verhalleman, Quinten; Richter, Jute; Proesmans, Marijke; Decaluwé, Herbert; Debeer, Anne; Van Raemdonck, Dirk
Abstract: OBJECTIVES: The purpose of this study was to evaluate the diagnosis of, clinical signs of and strategy for congenital cystic adenomatoid malformations (CCAM). METHODS: In this retrospective study, patients who had thoracic surgery for CCAM lesions at the University Hospitals of Leuven from July 1993 to July 2016 were identified. Data on diagnosis, prenatal ultrasound findings, clinical signs, lesion site, CCAM type, associated anomalies, imaging, surgical approach and postoperative morbidity were reviewed. The Fisher exact and Mann–Whitney tests were used as appropriate. RESULTS: A total of 55 patients were identified with CCAM. In 65% (n = 36/55), CCAM was detected on prenatal ultrasound scans. Prenatal symptoms due to hydrops or mass effect were present in 22% (n = 8/36), 6 of whom eventually needed prenatal intervention (thoracoamniotic shunting or intrauterine puncture). Elective surgery was performed in 40% of patients (n = 22/55); others developed clinical signs that indicated the need for semi-urgent surgery, with clinical signs of pulmonary infection and respiratory distress being the most common. Most patients had a single lobectomy via a minithoracotomy. Postoperative complications and length of stay were significantly higher in patients with CCAM with preoperative clinical signs. CONCLUSIONS: Surgery in asymptomatic patients with CCAM can be performed safely with few postoperative complications and can be planned at a young age in patients with a high risk of developing clinical signs later in life. Abstract : Congenital cystic airway malformations (CCAM), also known as congenital pulmonary airway malformations (CPAM), are the most common congenital airway anomalies and include 95% of the pulmonary congenital cystic developmental disorders.